2013
DOI: 10.1021/ac400778b
|View full text |Cite
|
Sign up to set email alerts
|

Suspension Bead Array of the Single-Stranded Multiplex Polymerase Chain Reaction Amplicons for Enhanced Identification and Quantification of Multiple Pathogens

Abstract: Rapid identification of single and multiple infectious agents is vital in clinical settings and during biothreat attack. This study assesses the assay of single-stranded multiplex polymerase chain reaction (PCR) amplicons by suspension bead array (SSMP-SBA) for multiple pathogens identification in a single-tube reaction. A 15-plex assay for identification of 11 highly infectious pathogens was developed to evaluate the performance of SSMP-SBA. Pathogen-specific amplicons were obtained by sequential amplificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…This method is able to identify all agents present when mixtures of up to six different bacterial DNAs were assayed. The limit of detection for this assay is between 5 and 100 genomic copies for each of the 11 pathogens [42]. …”
Section: Diagnosticsmentioning
confidence: 99%
“…This method is able to identify all agents present when mixtures of up to six different bacterial DNAs were assayed. The limit of detection for this assay is between 5 and 100 genomic copies for each of the 11 pathogens [42]. …”
Section: Diagnosticsmentioning
confidence: 99%
“…PCR amplification—a classical method used for ultrasensitive detection of nucleic acids—has also been used for the pre-amplification step in suspension arrays. 255 Chan et al 256 used an isothermal amplification technology, termed recombinase polymerase amplification (RPA), 257 in QD barcode-based multiplexed detection. When compared to PCR technology, RPA offers a portable, low-cost method for nucleic acid analysis, which is ideally suited for point-of-care use.…”
Section: Optical Label and Signal Amplificationmentioning
confidence: 99%
“…It was very important to minimize the non-specific fluorescence adsorption on the encoded microbeads since the reverse primers for PCR were Cy5-labelled, and there were still a large number of unreacted fluorescent-labeled short-chain primers in the reaction system in the process of the amplification reaction. Previously, our group developed a surface chemistry to fabricate encoded magnetic microbeads with host-guest structures, where 8 layers of polyelectrolytes were assembled layer by layer in situ on the host beads to afford highly stable guest silica nanoparticle landing and covalently conjugating [22]. However, the multi-layer polymer coating caused extremely high non-specific adsorption during PCR.…”
Section: Characterization Of Encoded Magnetic Microbeadsmentioning
confidence: 99%
“…In general, different oligonucleotide probes were immobilized on microbeads with unique barcodes, and then different target molecules in the sample could be identified, captured and manipulated specifically by their corresponding barcoded microbeads, thus realizing highly multiplexed detection in one reaction tube. For instance, Hsu et al (2013) coupled DNA probes onto 15 Luminex microbead sets, and demonstrated the use of the suspension array to simultaneously identify and quantify 11 pathogens [22]. Our group has also developed a 3D encoding library of 100 dual-color barcoded microspheres with ultrahigh stability and extraordinary coding ability, and has utilized them for six-plex detection of influenza viruses and five-plex tumor marker [23,24].…”
Section: Introductionmentioning
confidence: 99%